Exigency or Expediency? Contextualizing Islamic Theocracy in the Nigerian Political Landscape: A Historical Perspective - Lateef, Abiola Muideen (Kashere Journal of Politics and International Relations, 2023)
Islam has become a major force in Nigerian politics. However, scholarship on political Islam in Nigeria has mostly capitalized on the introduction of Sharīʿah in some northern states of the country as a tactical attempt to foisting Islamic theocracy on Nigerians. While it is important to understand the depths of Islamic proclivities in politics, it is equally vital that attempts be made to relate it to broader socio-political tectonics in the complex Nigerian landscape in order to better appreciate the nature and trajectory of the Islamic Theocracy in Nigeria. Focusing on the institutional re-introduction of Sharīʿah in some states in Nigeria and its attendant theocratic threats, this paper advances two arguments. First, the success of Sharīʿah re-enactment could not be sustained for long as it was vigorously applied within the first four years of its introduction and began to lose steam thenceforth. Second, the strategic political decision-making position occupied by various Muslim political actors in the government and civil society in Nigeria has not given the necessary impetus in response to internal and external systemic challenges of an Islamic theocratic government. Obviously, practicing Islamic theocracy, while pursuing social, economic, and political development, could be a suitable model especially for heterogeneous societies. However, it appears to be less vital to the politics of Nigeria than is plausibly perceived.